(untitled) (Manarul Qur’an: Jurnal Ilmiah Studi Islam, 2022)
Conflict usually occurs due to the gathering of four main elements in a common time, namely the supporting context, the root of the conflict, the axis and the trigger. Once a conflict occurs, the next process is escalation, namely the use of tactics that are getting tougher, the wider the target or the more involved. Thus the spread of unclear understanding will certainly disturb religious and social life which further damages the joints of religious harmony. The religion that according to the Javanese is called as an ageman (clothing) that can make it beautiful, healthy, safe for the wearer and others, will actually be something scary. The plurality of Indonesian society is a reality, and in that plurality should not be allowed discriminatory attitudes and practices. So that religion is not always misused and used as a scapegoat as a source or justification for conflict.